Prevalence and genotype distribution of human papillomavirus among 29 263 women from the Longgang community of Shenzhen. (14th July 2021) - Chen, Tingting; Cai, Songtao; Lin, Jinbo; Yang, Xue; He, Xuesen; Tu, Changqing; Yang, Chunxia
Abstract: Background: Human papillomavirus (HPV) vaccination and screening have been demonstrated to be effective methods for controlling cervical cancer. To provide evidence for effective targeted interventions, we investigated the HPV prevalence and genotypic distribution in women of different age groups in the Longgang community of Shenzhen, China. Methods: A total of 29 263 women were enrolled in the Longgang District Central Hospital from January 2018 to October 2020. Cervical specimens were collected at enrolment. We used a polymerase chain reaction diagnostic kit to detect the genotypes of HPV. Results: The prevalence of overall, high-risk, probable high-risk (PHR) and low-risk HPV infection was 8.2% (95% confidence interval [CI] 7.9 to 8.5), 6.9% (95% CI 6.6 to 7.2), 0.9% (95% CI 0.8 to 1.1) and 1.6% (95% CI 1.5 to 1.8), respectively. High-risk HPV genotype infections accounted for 84.4% (95% CI 82.8 to 85.8) of the overall HPV infections. The five most predominant genotypes were HPV-52, HPV-16, HPV-58, HPV-53 and HPV-51. Conclusion: Our study found that the prevalence of HPV infection increased with age and women 55–59 y of age presented the highest HPV prevalence. As a PHR subtype, HPV-53 has a higher infection rate in women. HPV-52, HPV-16 and HPV-58 are common infection genotypes.